The Role of Chosen Essential Elements (Zn, Cu, Se, Fe, Mn) in Food for Special Medical Purposes (FSMPs) Dedicated to Oncology Patients—Critical Review: State-of-the-Art - Frydrych, Adrian; Krośniak, Mirosław; Jurowski, Kamil (Nutrients, 2023)
The scoping review aimed to characterise the role of selected essential elements (Zn, Cu, Se, Fe, Mn) in food for special medical purposes (FSMPs) aimed at oncology patients. The scope review was conducted using Scopus, Google Scholar, and Web of Science to find published references on this subject. Data from the reviewed literature were related to the physiological functions of the element in the body, and the effects of deficiencies and excesses, referring to the latest ESPEN and EFSA guidelines, among others. Important dietary indices/parameters based on the literature review are provided for each element. On the basis of the literature, data on the level of elements in patients with cancer were collected. The content of these elements in 100 mL of FSMPs was read from the manufacturers’ declarations. The literature has been provided on the importance of each element in cancer. Our findings show that the essential elements (Zn, Cu, Se, Fe, and Mn) of FSMPs for cancer patients are not adequately treated. We suggest solutions to ensure the safe use of FSMPs in oncology patients.